Is PONV still a problem in pediatric surgery: a prospective study of what children tell us - Messerer, Brigitte; Stijic, Marko; Sandner-Kiesling, Andreas; Brillinger, Johanna M.; Helm, Jasmin; Scheer, Jacqueline; Strohmeier, Christof Stefan; Avian, Alexander (Frontiers in Pediatrics, 2023)
Background Postoperative nausea and vomiting (PONV) is an unpleasant complication after surgery that commonly co-occurs with pain. Considering the high prevalence among pediatric patients, it is important to explore the main risk factors leading to PONV in order to optimize treatment strategies. The objectives of this study are as follows: (1) to determine the prevalence of PONV on the day of surgery by conducting interviews with pediatric patients, (2) to assess PONV prevalence in the recovery room and on the ward by analyzing nursing records, and (3) to collect information on PONV risk factors on the day of surgery and the following postoperative days. We wanted to investigate real-life scenarios rather than relying on artificially designed studies. Methods A prospective analysis [according to STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) guidelines] of PONV on the day of surgery and the following postoperative days was conducted by evaluating demographic and procedural parameters, as well as conducting interviews with the children under study. A total of 626 children and adolescents, ranging in age from 4 to 18 years, were interviewed on the ward following their surgery. The interviews were conducted using a questionnaire, as children aged 4 and above can participate in an outcome-based survey. Results On the day of surgery, several multivariable independent predictors were identified for PONV. The type of surgery was found to be a significant factor (p = 0.040) with the highest odds ratio (OR) in patients with procedural investigations [OR 5.9, 95% confidence interval (CI): 1.8–19.2], followed by abdominal surgery (OR 3.1, 95% CI: 0.9–11.1) when inguinal surgery was used as the reference category. In addition, the study identified several predictors, including the amount of fentanyl administered during anesthesia (µg/kg body weight) (OR 1.4, 95% CI: 1.1–1.8), intraoperative use of piritramide (OR 2.6, 95% CI: 1.5–4.4) and diclofenac (OR 2.0, 95% CI: 1. 3–3.1), opioid administration in the recovery room (OR 3.0, 95% CI: 1.9–4.7), and piritramide use on the ward (OR 4.5, 95% CI: 1.7–11.6). Conclusions The main risk factors for PONV include the intraoperative administration of opioids during the recovery room stay and at the ward, the intraoperative use of non-opioids (diclofenac), and the specific type of surgical procedure. Real-life data demonstrated that in clinical praxis, there is a gap between the adherence to established guidelines and the use of antiemetic prophylaxis in surgeries that are generally not associated with a high PONV prevalence. Further efforts are needed to improve the existing procedures and thus improve the overall outcome.